Dynasty Divided : A Family History of Russian and Ukrainian Nationalism - Baumann, Fabian, 1990- (Book collections on Project MUSE., 2023)
"This book is a study of rivaling nationalisms in nineteenth-century Kiev. It traces the story of the Shul'gin/Shul'hyn family, a political dynasty that split into Russian and Ukrainian nationalists, analyzing how they embraced national categories, cultivated their national self-images, and competed for the loyalties of Ukraine's population"--